3x-1=5x-3

Simple and best practice solution for 3x-1=5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-1=5x-3 equation:


Simplifying
3x + -1 = 5x + -3

Reorder the terms:
-1 + 3x = 5x + -3

Reorder the terms:
-1 + 3x = -3 + 5x

Solving
-1 + 3x = -3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-1 + 3x + -5x = -3 + 5x + -5x

Combine like terms: 3x + -5x = -2x
-1 + -2x = -3 + 5x + -5x

Combine like terms: 5x + -5x = 0
-1 + -2x = -3 + 0
-1 + -2x = -3

Add '1' to each side of the equation.
-1 + 1 + -2x = -3 + 1

Combine like terms: -1 + 1 = 0
0 + -2x = -3 + 1
-2x = -3 + 1

Combine like terms: -3 + 1 = -2
-2x = -2

Divide each side by '-2'.
x = 1

Simplifying
x = 1

See similar equations:

| 45=-14c | | x+y+6x+7y= | | 3/nn-4/5=1/5n | | 2a-12a= | | 6v+7=43 | | 15+5x=180 | | (y+4)-3y=1+y | | 60+(k+l)=k*2 | | 3(3+2b)=-2(5-4b) | | 2m=2m+12 | | y=x^2+12x+32are-4and-8 | | 45z^3+20z^2+9z+4= | | 6(u-7)-8u=-34 | | ax^2-12x-3=6 | | -3(2-9)-a=1 | | 5x-2=-21 | | 25-5x+x=18+3x | | 11b^3-6b^2+11b-6= | | 6(2x-6)-4(x+1)-16x= | | 4=6-2x+1 | | -0006=.02x | | 10x+4=30 | | -15h^3+-6h^4+30h^5= | | 5x+3=0.57 | | .35=1.5 | | 16b^2-48b+11=0 | | a=3(3b+4c) | | -53=9x | | 4+13n-2=8n+29-4n | | 3y-2=8-2y | | -81=-(1-7k)+3k | | H=-16t^2+32t+20 |

Equations solver categories